The Contribution of Academic Self-Concept to Students' Reading Interest - Marimbun Marimbun (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
The purpose of this study was to describe students' academic self-concept and reading interest as well as the contribution of academic self-concept to students' reading interest in Islamic Guidance and Counseling Study Program IAIN Langsa. The method used is correlational method and simple regression. The study population was Islamic Guidance and Counseling students in semesters 1, 3, and 5, totaling 192 students who were active in the 2020 school year. The sampling technique used the proportional stratified random sampling technique. The number of samples is 130 respondents. The instrument used to collect data is a Likert scale model. The results of the study describe students' academic self-concepts in the positive category of 85%, quite positive at 28.5%, and very positive at 39%. Students' reading interest in the medium category is 45%, high is 45%, very high is 7%, and low is 7%. Furthermore, the correlation coefficient of academic self-concept on students' reading interest is 23%. This research can be concluded that academic self-concept contributes significantly to students' reading interest.